ANALISIS KERJASAMA KEAMANAN FILIPINA DENGAN AMERIKA SERIKAT DAN CHINA DALAM KONFLIK KEPULAUAN SPRATLY (2016-2024) - Satriana, Grachella (Journal Social Politica, 2025)
The Spratly Islands dispute has emerged as a major source of tension in Southeast Asian geopolitics due to China's increasingly assertive territorial claims and artificial island-building activities. This study examines how the leadership transition from Rodrigo Duterte (2016-2022) to Ferdinand Marcos Jr. (2022-2024) fundamentally altered Philippine security cooperation with the United States in the context of the Spratly Islands conflict. Using a qualitative research methodology with explanatory analysis, this study integrates Neoclassical Realism theory with the concepts of bandwagoning and balancing to analyze how domestic factors mediate foreign policy responses to consistent external pressures. The findings suggest that despite facing identical structural threats from Chinese expansion in the Spratly Islands, the Philippines has adopted very different strategic approaches under different leaderships. Duterte's bandwagoning strategy, characterized by "quiet diplomacy" and economic accommodation, has succeeded in attracting Chinese investment commitments but has failed to prevent China's continued militarization of artificial islands and the consolidation of de facto control over the disputed territory. In contrast, Marcos Jr.'s balancing strategy, which emphasized "transparency diplomacy" and the strengthening of US alliances through expanded access to military bases and increased joint exercises, effectively restored international credibility and enhanced deterrence, but actually increased the risk of direct confrontation. This research validates the core proposition of Neoclassical Realism that domestic factors serve as crucial mediating variables shaping how small states respond to external pressures.